Design, analysis and fabrication of portable dish washer / Muhammad Fakhrurazi Abdul Razak and Norjasween Abdul Malik - Abdul Razak, Muhammad Fakhrurazi; Abdul Malik, Norjasween (School of Mechanical Engineering, 2022)
Dish washing is a daily activity across the globe which involves a lot of energy to accomplish manually or mechanically. The objective of this project is to design and fabricate a portable dish washer that is efficient to use due to the difficulties faced in washing the dish. The main problem is it takes a long time to clean the dishes and uses a lot of energy. My idea is to clean the dish and consume less energy. This product is powered by a DC motor. This is because it is more efficient and makes better use of their input energy. The eco-friendly portable dish washer with an affordable price will benefit the lower-income family